2018
DOI: 10.1002/chem.201804463
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Cu2O Crystals for Diverse Aryl Alkyne Hydroboration Reactions

Abstract: Cu 2 Oc ubes,o ctahedra, and rhombic dodecahedra have been used to examine facet-dependent catalytic activity in aryl alkyneh ydroboration reactions. Althought he reaction can proceed by using ethanol or other alcohols as solvent, the use of 1,4-dioxane gave the bestp roduct yield. All particles hapes gave exclusively the E-product,b ut the rhombic dodecahedrae xposing {110} surfacesw ere consis-tently far more reactive than the other particlem orphologies. Ap roduct yield of 99 %w as achievedb yu sing Cu 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The 3d transition metals are earth‐abundant and demonstrate less toxic behavior, which makes them one of the prior choices for catalysis. In this regard, various first‐row transition metals are also used as efficient catalysts in syn ‐selective hydroboration, for instance, Ti, [48,49] Mn, [50] Fe, [51–58] Co, [59–61] Ni, [62] Cu, [63–77] and Zn [78] …”
Section: Syn‐hydroboration Of Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3d transition metals are earth‐abundant and demonstrate less toxic behavior, which makes them one of the prior choices for catalysis. In this regard, various first‐row transition metals are also used as efficient catalysts in syn ‐selective hydroboration, for instance, Ti, [48,49] Mn, [50] Fe, [51–58] Co, [59–61] Ni, [62] Cu, [63–77] and Zn [78] …”
Section: Syn‐hydroboration Of Alkynesmentioning
confidence: 99%
“…Cu catalysts have contributed significantly to hydroboration of alkynes in a highly stereo‐ and regioselective manner [63–77] . It is worthy of mention that the β‐ or α‐selective borylation of aromatic substituted unsymmetrical internal alkynes (such as 32 or 34 ) was achieved by varying the borylating reagents.…”
Section: Syn‐hydroboration Of Alkynesmentioning
confidence: 99%
“…The more ionic Cu-O bond leads to the catalytic production of important compounds, vinylboronates, a versatile class of intermediates for construction of numerous valuable complex molecules. [20][21][22][23] For now, the heterogeneous catalytic hydroboration of alkynes presents a straightforward and cost-efficient approach to access these vinylboronates [24][25][26][27][28][29][30] but generally suffering from the requirement of ligands or bases as additional additives, which results in higher costs and more waste in the reaction. In this work, a melamine-formaldehyde resin (MF) coating layer between Cu atoms and the ceria can decompose and disappear from the high temperature heat treatment, resulting in the more ionic Cu-O bond in the final catalyst (denoted as Cu 1 -O(I)/CeO 2 ).…”
Section: The Bigger Picturementioning
confidence: 99%
“…For now, the heterogeneous catalytic hydroboration of alkynes mainly depends on supported Cu catalysts. [24][25][26][27][28][29] These catalysts require ligands or bases as necessary additives because they can facilitate the formation of the crucial boryl copper species and thus promote the reaction pathway. [50][51][52] When these additives are absent, the hydroboration process is usually difficult to carry out smoothly.…”
Section: Catalytic Performance Evaluation For Hydroboration Of Alkynesmentioning
confidence: 99%
“…Cuprous oxide (Cu 2 O) is a p-type semiconductor with a small bandgap of ∼2.2 eV that possesses unique chemical and physical properties . Because of its well-known merits, including being inexpensive, earth-abundant, and nontoxic, it has a wide range of applications. For example, it can be used in catalysts, gas sensors, solar cells, batteries, chemical templates, and energy conversion . Various morphologies of Cu 2 O, including cubes, octahedra, , rhombic dodecahedra, , and hollow structures, were synthesized in previous studies, and it was found that different morphologies had different properties.…”
mentioning
confidence: 99%